The performance of an inexpensive spark-induced breakdown spectroscopy instrument for near real-time analysis of toxic metal particles. (1st November 2021) - Li, Hanyang; Mazzei, Leonardo; Wallis, Christopher D.; Davari, Seyyed Ali; Wexler, Anthony S.
Abstract: To meet the demand for identifying and controlling toxic air contaminants in environmental justice communities, we have recently developed a cost-effective spark-induced breakdown spectroscopy (SIBS) instrument for detecting and quantifying toxic metal air pollutants. We characterized the detection limit and linearity of this SIBS instrument by analyzing nebulized elemental standard solutions. The experimental parameters affecting SIBS performance were optimized, including the time delay to observation, the distance between electrodes, and the ablation voltage. The instrument successfully detected Cr, Cu, Mn, Fe, Zn, Co, and Ni, with limits of detection ranged from 0.05 μg m −3 to 0.81 μg m −3 at a flow rate of 15 l min −1 and a 30 min sampling duration. Similar to other investigations using ion breakdown spectroscopy, we did not observe strong emissions lines for As, Sb, Se, Hg, Pb, and Cd, which were likely due to spectral overlap, matrix effects, and the limited detection range of the optical components. Overall, SIBS is a promising technique for field measurements of toxic metals for environmental justice, industrial and urban applications. Highlights: We developed an inexpensive SIBS instrument for detecting toxic metal pollutants. The experimental parameters affecting SIBS performance were optimized. The instrument successfully detected Cr, Cu, Mn, Fe, Zn, Co, and Ni. We used univariate calibration to obtain detection limits (0.05–0.81 μg m −3 ).